divide by 3.
(x+2) (x-2) = 0
set both equal to 0
x= -2 and x= 2
Chat with our AI personalities
Without an equality sign and not knowing the plus or minus values of the given terms it follows that no solution is possible.
answer is p/5. problem: {[(p^2)-3p]/[(p^2)-6p+9]}/{20/(4p-12)}
The expression x2 + 1x - 12 can be factored out as (x - 3)(x + 4)
(n - 4)(n - 12)
a2 + 62 = 122 a2 + 62 - 62 = 122 - 62 a2 = 144 - 36 a2 = 108 taking the square root of each side, we get a equal plus or minus the square root of 108, or plus or minus 6 times the square root of 3.